Advanced Project Management Office: A Comprehensive Look at Function and Implementation, The - F Rad, Parviz (CRC Press, 2009)
The Project Management Office (PMO) is a rapidly emerging concept in project management that has evolved in terms of its application, sophistication, and proven results. Most literature on the subject focuses on a specific facet or purpose of PMO. The Advanced Project Management Office: A Comprehensive Look at Function and Implementation provides an all-inclusive description of the PMO and allows project management professionals to select the features most appropriate and relevant to the issues at hand, while keeping the full PMO picture in perspective. The authors illustrate how the PMO can be used to reduce costs of projects, decrease time to market for new products, increase corporate profits, and ensure project success.